La utilización de estrategias metodológicas y su incidencia en el desarrollo cognitivo de los niños y niñas de primer grado de educación general básica de la escuela “Domingo Faustino Sarmiento” de la ciudad de Ambato, cantón Pelileo, provincia de Tungurahua período lectivo 2013-2014”. Lineamientos alternativos - Cevallos Guerrero, Raquel Hortencia (2014)
This research refers to: "THE USE OF METHODOLOGICAL STRATEGIES AND ITS IMPACT ON BASIC EDUCATION FIRST GRADECHILDREN COGNITIVE DEVELOPMENT OF THE "DOMINGO FAUSTINO SARMIENTO" OF AMBATO CITY PELILEO CANTON, PROVINCE OF TUNGURAHUA PROVINCE PERIOD 2013- 2014 ". ALTERNATIVE GUIDELINES, whose general objective was to determine the incidence of the use of Methodological Strategies for the cognitive development ofBasic General Educationfirst grade children. The methodology used was mainly based on the Scientific Method, inductive, deductive, analytical, synthetic, descriptive and statistical model. The techniques that were applied, are the survey to the teachers to identify the use of Methodological Strategies, and the Cognitive Test to determine the Cognitive Development applied to children. 40% ofthe surveyed teachers use the gameas amethodological strategy, theChildren's Literature40%, and 20%Plastic Expression, so that teachersare responsible for thedesign, implementationand use ofstrategiesthat reflectworkinteresting for childreneducation. By applyingaCognitive Testwas determinedthat 94% ofchildrenwereplaced inthe highestlevel ofCognitive Developmentand 6%in thelow-level, encouraging them towork freely, creatingan atmosphere of trust, joy and especiallypromotethe game, it will help in all aspectsandareas of development